DEKONSTRUKSI DALAM VIRTUAL REALITY: ‘KEFFIYEH’ PADA WACANA WAR ON TERROR DAN VISUALISASI TOKOH UTAMA GAME FIRST PERSON SHOOTERS BERTEMA WAR ON TERROR - Kurniawan, Ivan (Majalah Ilmiah UNIKOM, 2018)
Development of computer graphics technology has been able to bring virtual reality to society. Games as part of virtual reality having high potential in changing the order of the people living in a visual culture. Phenomena and discourse in everyday life are often used as reference in making games. In line with that contained in the public discourse, the current game with the theme of the war against terrorism have high enthusiasm. But in addition to the similarity of the many outstanding game storylines, it is interesting to observe the use of the keffiyeh as the property of U.S. and NATO soldiers. Given the meaning of keffiyeh as a symbol of Palestinian resistance and opposing American politics coexist. This paper will review the kaffiyeh as a deconstruction of the elements in the discourse of 'war on terror' and first person shooters games with the theme of the war on terror, through a design standpoint and social impacts caused by the theory of deconstruction by Derrida.